(untitled) (Marketing Journal, 2026)
Abstract This study analysed the opportunities for developing trade services under conditions of an open economy. Using statistical data and theoretical approaches, the research evaluated the role of trade services in ensuring economic growth, competitiveness, and export potential. The findings showed that globalization processes, trade liberalization, development of logistics infrastructure, and the adoption of digital technologies influenced structural changes in the trade services market. The expansion of e-commerce platforms and logistics services contributed to improving the efficiency of trade activities. The results demonstrated that diversification of trade services, modernization of logistics systems, and the development of digital commerce supported the expansion of service exports in an open economy. Keywords: open economy, trade services, globalization, international trade, export potential, digital transformation, e-commerce, logistics infrastructure, competitive environment, economic integration.